2016
DOI: 10.1016/j.jhazmat.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Variations and factors that influence the formation of polychlorinated naphthalenes in cement kilns co-processing solid waste

Abstract: h i g h l i g h t s• PCN destruction efficiencies of cement kilns were derived.• Factors influencing PCN variation and formation were identified.• Major pathways for PCN formation and decomposition in cement kiln were discussed.• PCN indicators for sources involved with coal burning were proposed. a r t i c l e i n f o b s t r a c tPilot studies of unintentionally produced pollutants should be performed before waste being coprocessed in cement kilns. Polychlorinated naphthalene (PCN) formation and emission fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…This indicated that optimization of the operating conditions for stages at the kiln-end area and C1 preheater should be emphasized for inhibiting PCB formation. This is consistent with previous studies that reported high PCDD/F and PCN concentrations in samples from the SP boiler and humidifier tower, kiln-end bag filter, and C1 preheater Jin et al, 2016).…”
Section: Variation Of Pcb Concentrations Within the Kiln Systems Coprsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicated that optimization of the operating conditions for stages at the kiln-end area and C1 preheater should be emphasized for inhibiting PCB formation. This is consistent with previous studies that reported high PCDD/F and PCN concentrations in samples from the SP boiler and humidifier tower, kiln-end bag filter, and C1 preheater Jin et al, 2016).…”
Section: Variation Of Pcb Concentrations Within the Kiln Systems Coprsupporting
confidence: 93%
“…The techniques used in the three runs and the sampling sites are shown in Fig. 1, and were similar to those in a previous study (Jin et al, 2016).…”
Section: Methodsmentioning
confidence: 59%
“…The concentrations of Cl-PAHs and Br-PAHs in both stack gas and solid residues varied largely among facilities. The composition of feeding materials is an important factor influencing the formation of unintentional POPs, 42,43 whereas fractions of scrap copper is the important factor influencing the formation and release of POPs. 20 In this study, the concentrations of Cl-PAHs and Br-PAHs in the fly ash of plant C5, which used the 100% scrap copper with many more organic residues as the raw materials, were highest, which further confirmed the important influence of raw material composition on the emission levels of Cl-PAHs and Br-PAHs.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The advantages of co-processing of hazardous waste in a cement kiln include high incineration temperature, stable burning state, the neutralization of acid waste gas, long retention time, greenhouse gas emission reduction and low cost (Lamas et al, 2013; Liu and Zhang, 2011). Thus, cement kilns have become important facilities for disposing of hazardous waste in many countries (Jin et al, 2016; Sarc et al, 2014; Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%